ANALISIS STRATEGI KOMUNIKASI PEMASARAN (Studi Kasus Strategi Komunikasi Pemasaran Produk Tempo Coffee Cikarang) - Yudhistira, Fazar; Retno, Enlynia; Fadhilla , Ivan (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
This study aims to analyze the marketing communication strategies implemented by Tempo Coffee in Cikarang to enhance brand awareness and customer engagement. Using a case study approach, the research examines various communication channels and promotional tactics employed by the company. Data collection methods include interviews with management, observations, and analysis of marketing materials. The findings indicate that Tempo Coffee integrates digital marketing, social media promotions, and experiential marketing to reach its target audience effectively. However, challenges such as market competition and brand differentiation remain significant. The study concludes with recommendations for optimizing integrated marketing communication strategies to strengthen Tempo Coffee’s market position